A Comparative Study on the Calibration Systems of Soil-Test based Fertilizer Recommendations for Toria (Brassica campestris L.) in a Mollisol - and R. Chandra, Yeshpal, R.S. Sachan (Journal of the Indian Society of Soil Science, 2014)
A field experiment was conducted on a Mollisol with toria (Brassica campestris L.) as the test crop to study its response to selected combinations of 5 levels of N, 4 levels of P and 3 levels of K through fertilizers at different artificially created conditions and initial soil fertility at a single location. The response data were statistically treated for different calibration systems commonly employed to formulate soil-test based fertilizer recommendations, viz., regression model, targeted yield approach, Mitscherlich’s equation and soil testing laboratory recommendations being followed in the area. The targeted yield approach was found most suitable for fertilizer recommendation to toria (Brassica campestris L.) on Mollisol.